Assessment of p-nitroso dimethylaniline (pNDA) suitability as a hydroxyl radical probe: Investigating bleaching mechanism using immobilized zero-valent iron nanoparticles - Mortazavian, Soroosh; Bandala, Erick R.; Bae, Jee Hwan; Chun, Dongwon; Moon, Jaeyun (ELSEVIER SCIENCE SA, 2020)
Use of p-nitroso dimethylaniline (pNDA) as a selective hydroxyl radical (center dot OH) probe compound has been extensively reported in the literature for evaluating the performance of the catalysts used in Advanced Oxidation Processes (A0Ps). Some recent studies speculated that pNDA might be oxidized by other oxidizing species, and might also be directly reduced. This study, for the first time, investigates pNDA bleaching mechanism by an Fe-0- containing composite, capable of causing both reduction and Fenton-like oxidation. The composite consisted of Santa Barbara-15 (SBA-15) mesoporous silica as the supporting medium for nZVI immobilization (nZVI/SBA-15). The quantity of iron in the composite was optimized by synthesizing four various nZVI/SBA-15 samples with different iron to silica weight ratios and comparing their pNDA bleaching efficiency. Kinetic studies showed a pseudo-second-order model for pNDA bleaching using all nZVI/SBA-15 samples. The effects of center dot OH scavengers and dissolved oxygen concentration on pNDA bleaching rate were examined. FTIR analysis of pNDA solutions showed different molecular structures for pNDA bleached under different DO conditions, leading to the conclusion that pNDA is susceptible to reductive bleaching. Results demonstrated that when using pNDA as a probe for free radicals' generation assessment, the reductive potential of the catalysts needs to be considered.